Preparation of polymeric derivative from cassava starch (manihot esculenta crantz) and its application as flocculant in waste water treatment - Osear Julio Medina Vargas, Munoz Prieto Efrén de J., Lucia Marlén Moreno Bastidas (Universidad Pedagógica y Tecnológica de Colombia, 2012)
Abstract Synthesis, identification  and  evaluation  of a  cationic flocculant,  from cassava starch in the  species (Manihot esculenta crantz), was conducted, at  Pedagogical  and  Technological  University  of  Colombia,  UPTC, Chemistry Laboratory. The extraction process of native cassava starch, a proximate  analysis,  synthesized  polymer,  was  identified  by  comparing their  structural characteristks with the starch, using apparent viscosity, X-ray diffraction X-RO,  infrared spectroscopy FTIR, and scanning electron microscopy SEM. Ajar test was done to determine its effectiveness as a flocculant,  and  the results made it possible to elucidate their structure after its modification. The  importance  of this work  is  that a  cationic modified starch derivative can be used as coadjutant in  the flocculation process, in waste water  treatment, which is an important contribution to socio-economic community progress  in  the region, where  this  plant is growing. Keywords: Cationic starch, Modified  starch,  Extraction,  ldentification, Flocculation Resumen La sintesis, identificación y evaluación de un floculante catiónico, obtenido a partir del almidón de yuca de la especie (Manihot esculenta Crantz),  se llevó a cabo el proceso de extracción del almidón de yuca, en el laboratorio de quimica  de  la  UPTC,  análisis  proximal,  la  sintesis,  del  polimero,  su identificación y la comparación de sus características estructurales con el almidón nativo,  tales como: viscosidad aparente, difracción de rayos X,  (X-RO),  espectroscopia infrarroja  (FTIR)  y microscopia electrónica de barrido (SEM). A  continuación, pruebas de  jarras, fueron realizadas para determinar la eficacia de los derivados cationicos como floculantes,  los resultados han permitido elucidar  su estructura después de  su modificación. La importancia de este trabajo es que el almidón  catiónico modificado,  puede utilizarse como coadyudante en el proceso de  floculación en el tratamiento de aguas, que es una importante contribución a  la comunidad socio-económica en la región donde se  desarrolle  este  cultivo. Palabras  claves:  Almidón  catiónico,  almidón  modificado,  extracción, dentificación, floculación.